(untitled) (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Cancer has caused nearly 10 million deaths globally in 2020, accounting for one-sixth of all fatalities. Although chemotherapy can be effective in some cases, it often fails to treat solid tumors effectively because of their biological diversity and uncontrolled growth. Chemotherapy can also be toxic, particularly when multiple drugs are used. This study aimed to investigate the potential of combining low-molecular-weight pectin and metformin with chemotherapy in Walker carcinoma cells. Materials and Methods: This study was conducted using white-outbred Wistar rats. Tumors were transplanted subcutaneously, and the animals were then treated with pectin and metformin administered intragastrically using a probe, whereas cytostatic agents were administered intraperitoneally. Antitumor activity was assessed based on three parameters: tumor growth inhibition (TGI), survival/increase in life span (ILS), and average lifespan. Results: The combination of pectin and doxorubicin had the most significant antitumor effect (TGI 88.66% and ILS 142.22%) compared to the combination of metformin and cytostatic agents. In a series of experiments with fluorouracil, a notable antitumor effect was observed with the combination of fluorouracil and metformin (TGI, 89.6%). Conclusion: This study demonstrated that combined therapy with modified citrus pectin and doxorubicin led to higher antitumor effects and ILS than doxorubicin monotherapy. In addition, the combination of metformin and fluorouracil showed the potential to increase survival rates, suggesting its potential detoxifying properties.